Cannabinoid receptor CB2 localisation and agonist-mediated inhibition of capsaicin responses in human sensory neurons. - Anand, U; Otto, W; Sanchez-Herrera, D; Facer, P; Yiangou, Y; Korchev, Y; Birch, R; Benham, C; Bountra, C; Chessell, I; Anand, P (2008)
Cannabinoid receptor 2 (CB2) agonists provide the potential for treating chronic pain states without CNS effects associated with CB1 receptor activation. Animal models suggest that they act mainly via non-neuronal cells, possibly inhibition of inflammatory cells in the periphery or CNS, or via release of beta-endorphin; however, the clinical relevance and mechanism of analgesic action is uncertain. Here, we demonstrate colocalisation of CB2 with CB1 and the capsaicin receptor TRPV1 in human dorsal root ganglion (DRG) sensory neurons and increased levels of CB2 receptors in human peripheral nerves after injury, particularly painful neuromas. In primary cultures of human DRG neurons, selective CB2 agonists blocked activation of inward cation currents and elevation of cytoplasmic Ca2+ in response to capsaicin. These inhibitory effects were reversed by GW818646X a CB2 antagonist, and 8-bromo cAMP, but not by SR141716 a CB1 antagonist, or naloxone. Thus CB2 receptor agonists functionally inhibited nociceptive signalling in human primary sensory neurons via a mechanism shared with opioids, of adenylyl cyclase inhibition, but not via mu-opioid receptors. We conclude that CB2 agonists deserve imminent clinical trials for nociceptive, inflammatory and neuropathic chronic pain, in which capsaicin or heat-activated responses via TRPV1 may provide a clinical marker.